Persistent Identifiers: the ‘URN Granular’ Project of the German National Library and the University and State Library Halle - Sommer, Dorothea (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2010)
This paper describes a project carried out by the German National Library, the University and State Library Sachsen-Anhalt in Halle and Semantics GmbH Aachen to establish routines of persistent identification for individual pages of web publications in order to enable and facilitate reliable and long-term valid citation practices for the academic community. The project originated in a pilot project to digitise approximately 10,000 German imprints from the seventeenth century comprising altogether about 600,000 pages, which had to be completed within two years. The material of the ‘Ponickau Collection’ had been catalogued in the German national bibliography of seventeenth-century imprints (VD 17), which was enriched and turned into a virtual library by adding the digitised texts. This article investigates the means of presentation and indexing of digitised imprints in order to ensure their usability. It also sketches the workflow among the various partners involved in the process. The article highlights the application of Visual Library, which contains various tools for automated creation of metadata, the implementation of persistent identifiers (URN) and the automated enrichment of catalogue entries by the regional cataloguing cooperative Gemeinsamer Bibliotheksverbund (GBV). Special emphasis is given to questions of quality management; the quality is guaranteed by a combination of automated tools and intellectual control at various stages of the digitisation process.